EFFECTS OF LOAN DEFAULT ON FINANCIAL PERFORMANCE IN COOPERATIVE THRIFT AND CREDIT SOCIETIES IN KWARA-STATE NIGERIA - Adebayo, O.M.; Jimoh, B.O.; Ademola, A.O.; Ayinde, O.V.; Adebowale, S.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigated the impact of loan default on financial performance of Cooperative Thrift and Credit Societies (CTCSs) in Kwara-State of Nigeria. Specifically, it examined how employment instability and financial distress. Primary data were obtained through structured questionnaires and interviews with CTCS management, lending committees, trustees, and members. Out of 198 instruments distributed, 191 valid responses were analyzed using both descriptive and inferential statistical tools, including frequency distributions and multiple regression analysis. Demographic findings revealed that 52.0% of respondents were female, and 86.9% were married. The average age was 31 years, with an average of 13 years experience in cooperative participation. More than half (51.8) of the respondents had formal education, with an average household size of six. Additionally, 52.8% of the respondents had been members for 6 to 10 years, and 90.0% held membership roles, indicating strong engagement and potential influence on cooperative operations. Regression results indicated that employment instability, particularly unemployment (coefficient = -.677, p = 0.030) and irregular income (coefficient = -.342, p = 0.020), significantly increased loan default risk. Financial distress, reflected in frequent emergency loan requests, negatively affected interest income which affects financial stability of members which reduces repayment rates decline, the cooperative earns less interest from loans, directly affecting its financial sustainability. It is therefore recommended that cooperatives enforce stricter loan eligibility criteria and implement structured debt repayment plans.